Pengaruh Pembiayaan Bank Syariah dan Kredit Bank Konvensional Terhadap Pertumbuhan Ekonomi di Indonesia - Serly Angrayni; Hasdi Aimon; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This research purpose are to the analyse the how the impact of dependent variables, there are Sharia Financing, Commercial Credit, Inflation, Government Expenditure, and Human Development in terms of the Economic Growth in Indonesia. Methods that being used are Panel Least Square and used Fixed Effect Model, the estimation results show that Sharia Financing has a positive effect but not significant on Economic Growth in Indonesia, Credit Commercial has a significant positive effect on Economic Growth in Indonesia, Inflation has a significant negative effect on Economic Growth in Indonesia, Government Expenditure has a significant positive effect on Economic Growth in Indonesia, and Human Development has a significant positive effect on Economic Growth in Indonesia.